2021
DOI: 10.3389/fdgth.2021.719138
|View full text |Cite
|
Sign up to set email alerts
|

Successful Multi-Level HPV Vaccination Intervention at a Rural Healthcare Center in the Era of COVID-19

Abstract: Objectives: To develop and test a human papillomavirus (HPV) vaccination intervention that includes healthcare team training activities and patient reminders to reduce missed opportunities and improves the rate of appointment scheduling for HPV vaccination in a rural medical clinic in the United States.Methods: The multi-level and multi-component intervention included healthcare team training activities and the distribution of patient education materials along with technology-based patient HPV vaccination remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It is anticipated that this critical intervention will reduce missed opportunities for HPV vaccination and thereby minimize the potential longterm consequences on incident HPV infections and associated sequelae as a result of the COVID-19-related disruptions. Maintaining school-based HPV vaccine delivery strategies and catch-up programmes, in combination with intensified social mobilization and community awareness campaigns, as well as ensuring strong provider recommendations and reminders, have all been cited as key interventions for overcoming barriers to HPV vaccination during the COVID-19 era (20,44).…”
Section: Supply-side Determinants Of Programme Performancementioning
confidence: 99%
“…It is anticipated that this critical intervention will reduce missed opportunities for HPV vaccination and thereby minimize the potential longterm consequences on incident HPV infections and associated sequelae as a result of the COVID-19-related disruptions. Maintaining school-based HPV vaccine delivery strategies and catch-up programmes, in combination with intensified social mobilization and community awareness campaigns, as well as ensuring strong provider recommendations and reminders, have all been cited as key interventions for overcoming barriers to HPV vaccination during the COVID-19 era (20,44).…”
Section: Supply-side Determinants Of Programme Performancementioning
confidence: 99%
“…Although the data presented in the current study do not distinguish between urban and rural areas, previous studies have indicated that, in populations with high vaccination rates, the percentage of HPV vaccination in rural areas is 10% lower than in urban areas. This is due to several factors, including lower public awareness, a reduced interest in conducting preventative activities by medical personnel, and a limited number of outlets providing medical services [73]. For countries such as Poland, where a significant proportion of the country's population lives in rural areas, it is critical to develop methods to promote prophylactic HPV vaccination in these regions.…”
Section: Human Papillomavirus Vaccinationmentioning
confidence: 99%
“…The gender gap in HPV vaccination is magnified in the rural setting, with the HPV vaccination rates of boys ages 13–17 only 5.31% and 5.5% in isolated small rural towns and rural towns, respectively, compared with 30% and 26.8% in girls [ 15 , 18 ]. A recent study demonstrated that rates of HPV vaccination could be improved in a rural setting with interventions including healthcare team training activities and distribution of patient education materials along with technology-based patient HPV vaccination reminders for parents and caregivers and young adult patients [ 19 ]. The combination of low vaccination rates and rising HPV oropharynx cancer cases in rural areas sets the stage for a worsening health disparity for decades unless urgent attention is paid to increasing HPV vaccination in rural communities.…”
Section: Ruralitymentioning
confidence: 99%